Identification of Selective Sweeps in the Domesticated Table and Wine Grape (Vitis vinifera L.) - Kui, Ling; Tang, Min; Duan, Shengchang; Wang, Shouling; Dong, Xiao (Frontiers in Plant Science, 2020)
Grapevine (Vitis vinifera), one of the most important fruit species in the Classical Mediterranean world, is thought to have been domesticated 6,000 – 8,000 years ago in the Near East. However, the domestication process of its wild relative into wine grapes or table grapes remains largely unknown. In this study, we randomly selected 30 table grapes, 30 wine grapes and 30 dual-purpose grape accessions, as well as 30 wild relatives (Vitis vinifera ssp. sylvestris). The phenotypic comparison showed striking differences in berry weight, acidity and the content of aroma. Based on a total of 7,522,958 single-nucleotide polymorphisms, we identified several significant selective sweep regions for table and wine grapes. Besides the well-known sex-determination locus on chromosome 2, the other 4 highest signals shared by two groups could not be linked to the known QTLs. The identification of these genomic regions under selection sweep may reveal agronomically important traits that have been selected during grape domestication. This information could not only shed light on the mechanisms of adaptions and diversification, but also guide the genetic improvement in breeding programs.